Cross-sectional study of the association between functional status and acute kidney injury in geriatric patients. Issue 1 (December 2015) - Chao, Chia-Ter; Tsai, Hung-Bin; Wu, Chia-Yi; Hsu, Nin-Chieh; Lin, Yu-Feng; Chen, Jin-Shing; Hung, Kuan-Yu
Abstract Background Patients with chronic kidney disease tend to have impaired functional status, and this can increase the risk of morbidity and mortality. However, no previous studies have rigorously evaluated the relationship between incident acute kidney injury (AKI) and functional status of elderly patients. Methods Elderly patients (≥65 years-old) were prospectively from the general medical wards of a single medical center in Taiwan between January, 2014 and August, 2014. These patients were divided into those with and without AKI at initial presentation, according to Kidney Disease Improving Global Outcomes (KDIGO) criteria. Functional status was assessed by Barthel Index on admission. Multiple regression analyses were utilized to investigate the relationship between AKI and functional status. Results One hundred and fifty-two elderly patients were recruited, 38.9 % of whom had AKI. Patients with AKI at admission had significantly higher mean Charlson Comorbidity Index score (p  = 0.05) and borderline lower mean Barthel Index score (34.5vs. 43.1;p  = 0.08), and a significantly lower bladder continence subscale (5.4 vs. 7.0;p  = 0.05). Multiple regression analyses indicated that the presence of AKI at admission was associated with a significantly lower Barthel Index score (p  = 0.04). Increasing AKI severity (higher KDIGO stage) was also associated with significantly lower Barthel Index score (p <0.01). Conclusions This study documented a close relationship between AKI and functional status in the elderly. Interventions that aim to restore functional status might help to lower the risk of AKI in the elderly.